The myxozoans Myxobolus cerebralis and Tetracapsuloides bryosalmonae modulate rainbow trout immune responses: quantitative shotgun proteomics at the portals of entry after single and co-infections - Saleh, Mona; Hummel, Karin; Schlosser, Sarah; Razzazi-Fazeli, Ebrahim; Bartholomew, Jerri L.; Holzer, Astrid; Secombes, Christopher J.; El-Matbouli, Mansour (Frontiers in Cellular and Infection Microbiology, 2024)
Introduction Little is known about the proteomic changes at the portals of entry in rainbow trout after infection with the myxozoan parasites, Myxobolus cerebralis, and Tetracapsuloides bryosalmonae. Whirling disease (WD) is a severe disease of salmonids, caused by the myxosporean M. cerebralis, while, proliferative kidney disease (PKD) is caused by T. bryosalmonae, which instead belongs to the class Malacosporea. Climate change is providing more suitable conditions for myxozoan parasites lifecycle, posing a high risk to salmonid aquaculture and contributing to the decline of wild trout populations in North America and Europe. Therefore, the aim of this study was to provide the first proteomic profiles of the host in the search for evasion strategies during single and coinfection with M. cerebralis and T. bryosalmonae. Methods One group of fish was initially infected with M. cerebralis and another group with T. bryosalmonae. After 30 days, half of the fish in each group were co-infected with the other parasite. Using a quantitative proteomic approach, we investigated proteomic changes in the caudal fins and gills of rainbow trout before and after co-infection. Results In the caudal fins, 16 proteins were differentially regulated post exposure to M. cerebralis, whereas 27 proteins were differentially modulated in the gills of the infected rainbow trout post exposure to T. bryosalmonae. After co-infection, 4 proteins involved in parasite recognition and the regulation of host immune responses were differentially modulated between the groups in the caudal fin. In the gills, 11 proteins involved in parasite recognition and host immunity, including 4 myxozoan proteins predicted to be virulence factors, were differentially modulated. Discussion The results of this study increase our knowledge on rainbow trout co-infections by myxozoan parasites and rainbow trout immune responses against myxozoans at the portals of entry, supporting a better understanding of these host-parasite interactions.